Prospek Ekonomi Peremajaan Perkebunan Kelapa Sawit Rakyat: Analisis Kelayakan di Tingkat Petani, Kabupaten Nagan Raya - Irawan, Heri Tri; Arga, Dwi Prasiska Lena; Hasnita, Hasnita; Pandria, T.M. Azis; Ulhaq, Riza; Pamungkas, Iing; Hadi, Khairul; Saputra, Arie; Muzakir, Muzakir (Universitas Teuku Umar, 2025)
This research aims to analyze the financial feasibility and sensitivity of investment in the rejuvenation of smallholder oil palm plantations in Lungmane Village, Kuala Pesisir Subdistrict, Nagan Raya Regency, Aceh Province, amidst the problem of declining Fresh Fruit Bunch (FFB) productivity due to aging trees. The research method used is quantitative analysis with investment criteria of Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit-Cost Ratio (Net B/C), and Payback Period (PP), as well as sensitivity analysis to changes in FFB prices. The results of the analysis show that the rejuvenation project for smallholder oil palm plantations in Lungmane Village is financially feasible based on positive NPV, IRR, Net B/C, and Payback Period indicators. However, the sensitivity analysis reveals that the project's feasibility is highly influenced by fluctuations in FFB prices, where a price decrease of up to 70% can render the project unfeasible. This study concludes that although the rejuvenation of smallholder oil palm plantations in Lungmane Village has good financial prospects, farmers need to be aware of the risk of declining FFB prices.